Administering Windows server 2008 server core - Mueller, John (Sybex/Wiley Pub., 2008)
Microsoft's new GUI-less Server Core is a command line version of Windows Server 2008 that offers better security, reduced size, and faster access. Inside this comprehensive guide, you'll find everything you need to quickly master this sleek new version. Packed with instructions and practical examples, this book teaches you how to operate in a windowless environment, including using all the commands, creating BAT files, working with scripts, using registry hacks, managing remote systems, and more. Includes best practices, 52 indispensable command line tricks, and an alphabetical list of all the commands.